Hexanal as a marker of oxidation flavour in sliced and uncured deli turkey with and without phosphates using rosemary extracts. (8th April 2020) - Bak, Kathrine Holmgaard; Rankin, Scott A.; Richards, Mark P.
Summary: Ability of commercial rosemary extracts (REs) alone and in combination with sodium tripolyphosphate (P) to inhibit lipid oxidation in uncured deli turkey (UDT) was examined via headspace hexanal and oxidation flavour. Sliced UDT was packaged (75% N2 /25% CO2 ) and stored 13 weeks at 4 °C. Addition of P decreased hexanal 2.4‐fold ( P  < 0.05) and increased mean pH of UDT from 5.94 to 6.30 ( P  < 0.05). Addition of water/lipid‐soluble RE did not inhibit hexanal formation in UDT. Addition of water‐soluble RE decreased hexanal 2.2‐fold ( P  < 0.05). The combination of P and water‐soluble RE decreased hexanal 33‐fold ( P  < 0.05). The combination of P and water/lipid‐soluble RE decreased hexanal ninefold ( P  < 0.05). Oxidation flavour was highest in UDT without added antioxidant> RE> P> RE+P ( P  < 0.05). Hexanal values were positively correlated with oxidation flavour scores throughout storage ( P  < 0.05). The combination of P with either RE was particularly effective at inhibiting lipid oxidation in modified atmosphere packaged UDT. Abstract : Rosemary extract was added to sliced, uncured deli turkey with and without phosphate. Oxidation was measured at weeks 1, 7 and 13 as headspace hexanal and oxidation flavour. Both phosphate and rosemary reduced oxidation. Correlation models between headspace hexanal and oxidation flavour were made.